2021
DOI: 10.1016/j.ajic.2021.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Environmental testing for SARS-CoV-2 in three tertiary-care hospitals during the peak of the third COVID-19 wave

Abstract: Contamination of surfaces has been implicated in transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We tested by real-time PCR for SARS-CoV-2 contamination environmental samples from three hospitals during the peak of the third pandemic wave. Overall, 19 of 463 (4.1%) samples tested positive: 12 of 173 (6.9%) samples from a COVID-19 hospital, 3 of 177 (1.7%) samples from a non-COVID-19 hospital, and 4 of 113 (3.5%) samples from a pediatric hospital with dedicated COVID-19 clinics. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The highest positivity rates regarding SARS-CoV-2 were found in samples collected from COVID-19 patients’ rooms. SARS-CoV-2 RNA has been frequently detected in surfaces surrounding COVID-19 patients [ 39 ]; however, detection does not imply infectiousness [ 40 ]. Previous studies have shown that the virus is able to survive on various porous and non-porous surfaces, such asglass, steel, or certain types of plastic [ 41 ], and for up to 28 days at 20 °C [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The highest positivity rates regarding SARS-CoV-2 were found in samples collected from COVID-19 patients’ rooms. SARS-CoV-2 RNA has been frequently detected in surfaces surrounding COVID-19 patients [ 39 ]; however, detection does not imply infectiousness [ 40 ]. Previous studies have shown that the virus is able to survive on various porous and non-porous surfaces, such asglass, steel, or certain types of plastic [ 41 ], and for up to 28 days at 20 °C [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a highly sensitive PCR panel that can detect variant markers would be ideal for wastewater monitoring ( 58 ). Similarly, the variant panel may also be a useful, cheaper alternative to sequencing and in vitro diagnostic (IVD) PCR assays for other types of environmental/non-clinical testing ( 59 ) (e.g., contamination/decontamination verification) ( 60 ), as RUO assays are typically less expensive than IVD assays. Although not the focus of this study, very limited preliminary studies have also been conducted using our RT-qPCR assays to test for SARS-CoV-2 variants in wastewater samples (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Most environmental surveillance studies conducted since early 2020 have focused on assessing the internal source of contamination by monitoring isolation wards ( [11] , [12] , [13] , [14] , [15] ), Intensive Care Units (ICU) ( [16] , [17] , [18] , [19] ) and general wards ( 15 , 18 , 19 ). The risk of external introduction has also been assessed in other healthcare facilities, including the Emergency Departments (ED) ( 15 , [20] , [21] , [22] , [23] , [24] ), but were mainly conducted during the peaks of the epidemic in short study periods. Previous studies have reported a highly variable detection frequency of SARS-CoV-2 RNA from surface samples from both inpatient (2.5 - 48.1%) and outpatient (0 - 56.6%) facilities ( 15 , [20] , [21] , [22] , [23] , [24] ).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of external introduction has also been assessed in other healthcare facilities, including the Emergency Departments (ED) ( 15 , [20] , [21] , [22] , [23] , [24] ), but were mainly conducted during the peaks of the epidemic in short study periods. Previous studies have reported a highly variable detection frequency of SARS-CoV-2 RNA from surface samples from both inpatient (2.5 - 48.1%) and outpatient (0 - 56.6%) facilities ( 15 , [20] , [21] , [22] , [23] , [24] ). The detection frequencies reported by the short-term studies were confounded to delineate the external vs. internal source of contamination as samples were usually taken at the peak of epidemic waves with extensive SARS-CoV-2 community transmission.…”
Section: Introductionmentioning
confidence: 99%